2021
DOI: 10.1093/fpa/orab010
|View full text |Cite
|
Sign up to set email alerts
|

Role Legitimation in Foreign Policy: The Case of Indonesia as an Emerging Power under Yudhoyono's Presidency (2004–2014)

Abstract: This article analyzes how foreign policymakers legitimize their enactment of role conceptions to play a more active role at the global level toward a potentially reluctant domestic audience. In order to reduce the likelihood of domestic role contestation while at the same time subscribe toward ego and alter expectations, it is necessary for policymakers to legitimize role conceptions and their enactments toward domestic audiences. This article develops the notion of role legitimation to capture this process an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Much of the literature has shown that Indonesia is an emerging middle power because of its capability, diplomatic posture and growing international reputation as an emerging power especially during Yudhoyono’s presidency (2004–2014; Acharya, 2014; Fitriani, 2015; Karim, 2021). During his presidency, it appears that Indonesia tried its best to improve its standing in the international system—one of its many efforts is by exploiting Indonesia’s status as the world’s largest Muslim-majority country by repositioning itself to the status while sticking to secular democratic norms that are at the heart of Western civilisation (Karim, 2021).…”
Section: Role Conception Of Asia-pacific Middle Powers In Response To...mentioning
confidence: 99%
See 2 more Smart Citations
“…Much of the literature has shown that Indonesia is an emerging middle power because of its capability, diplomatic posture and growing international reputation as an emerging power especially during Yudhoyono’s presidency (2004–2014; Acharya, 2014; Fitriani, 2015; Karim, 2021). During his presidency, it appears that Indonesia tried its best to improve its standing in the international system—one of its many efforts is by exploiting Indonesia’s status as the world’s largest Muslim-majority country by repositioning itself to the status while sticking to secular democratic norms that are at the heart of Western civilisation (Karim, 2021).…”
Section: Role Conception Of Asia-pacific Middle Powers In Response To...mentioning
confidence: 99%
“…Despite Indonesia being of strategic importance to the US, the country chose not to align themselves with the US during the Cold War. After the collapse of Suharto’s authoritarian regime in 1998, Indonesia has transformed into a middle power after years of growth and stability (Karim, 2021). Indonesia is now the world’s third biggest democracy, the largest Muslim-majority country, the leader of ASEAN and a member of the G–20.…”
Section: Role Conception Of Asia-pacific Middle Powers In Response To...mentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of increasing ASEAN connectivity is to maintain ASEAN centrality amidst the growing regional tension. This is why Indonesia, as the largest country in Southeast Asia, puts so much emphasis on ASEAN connectivity, given Indonesia policymakers continue to view ASEAN as its priority for Indonesia's ambition to be a global player and regional manager (Karim, 2021;Rosyidin & Pattipeilohy, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia became one of the founding members of ASEAN in 1967 and enjoyed a recognition as an informal regional leader of the association in the 1970s until 1980s. Karim (2021) focuses on how President Susilo Bambang Yudhoyono (Yudhoyono, hereafter) tried to legitimize Indonesia's international leadership role by referring to Indonesia's historical experience in conducting such role and using international expectations to ensure domestic support for the president's foreign policy endeavor. Thus, Karim's argument points to the key role of a state leader in determining the nature of his foreign policy endeavor.…”
Section: Introductionmentioning
confidence: 99%